Human Papilloma Virus vaccine and cervical cancer screening acceptability among adults in Quebec, Canada - Duval Bernard; Sauvageau Chantal; Gilca Vladimir; Lavoie France; Ouakki Manale (BMC, 2007)
Abstract Background The Pap test has been used for cervical cancer screening for more than four decades. A human papillomavirus (HPV) vaccine has been approved for use in Canada and is commercially available now. These two preventive interventions should be considered simultaneously. General population support is an important factor for the successful combination of these interventions. The study had two objectives: 1) To assess practices, beliefs, and attitudes regarding Pap test screening and HPV immunization; 2) To identify socio-demographic factors for Pap screening and vaccine acceptability. Methods In 2006, 500 adults were invited to participate in a telephone survey in the region of Quebec City (urban and rural population, 600 000), Canada. Some neutral and standardized information on Pap test and HPV was provided before soliciting opinions. Results 471 adults (18-69 year-olds) answered the questionnaire, the mean age was 45 years, 67% were female, and 65% had college or university degree. Eighty-six percent of women had undergone at least one Pap-test in their life, 55% in the last year, and 15% from 1 to 3 years ago. Among screened women, the test had been performed in the last three years in 100% of 18-30 year-olds, but only in 67% of 60-69 year-olds (P < 0.0001). Only 15% of respondents had heard of HPV. Eighty-seven percent agreed that HPV vaccines could prevent cervical cancer, 73% that the vaccine has to be administered before the onset of sexual activity, 89% would recommend vaccination to their daughters and nieces. Among respondents < 25 years, 91% would agree to receive the vaccine if it is publicly funded, but only 72% would agree to pay $100/dose. Conclusion There is an important heterogeneity in cervical cancer screening frequency and coverage. Despite low awareness of HPV infection, the majority of respondents would recommend or are ready to receive the HPV vaccine, but the cost could prevent its acceptability.